Nomenclatural analysis of validity of Taraxacum names published by J. L. van Soest after 1958 - Kirschner, Jan; Štěpánek, Jan (Phytotaxa, 2014)
A revision of names published by J. L. van Soest (1898–1983) after 1958 revealed a number of names of doubtful validity. A detailed nomeclatural analysis of the validity of these names revealed that, from the point of view of the typification methods of van Soest, there are ten categories of names, many of them requiring validation. All the relevant names were studied and the problematic names are listed. There are 27 names with more than one specimen of a single gathering cited (20 are lectotypified). Another 19 names are listed that were typified by van Soest only in the captions to figures accompanying the text. Many names were found invalid; of these, eight names were validated later by van Soest or other authors, another 15 names were not considered as taxonomically sound by the present authors (and remained invalid). The following 15 names are validated and therefore published as new here, with the authorship of J. L. van Soest retained, Art. 46, Ex. 20): Taraxacum luteocucullatum, T. elegans, T. fulvobrunneum, T. nagaricum, T. sordidepapposum, T. vulpinum, T. brakelii, T. flavum, T. pseudoeriopodum, T. pullocarpum, T. rufulum, T. tenuiceps, T. helianthum, T. phoenicolepis and T. stereodiforme (all mainly as a result of the conflict with Art. 40.1, 40.3, Ex. 3, or Art. 30.4, 30.5 of the Code).